Identification of the −α2.4 Deletion in One Family and in One Hb H Disease Patient in Guangxi, People's Republic of China. (3rd May 2016) - Pang, Wanrong; Sun, Lei; Long, Ju; Weng, Xunjin; Ye, Xuehe; Wang, Junjie; Liao, Yan; Tang, Weijun; Fan, Zuqian; Wu, Suping; Song, Chuanlu; Wei, Xiaoying; et al.
Abstract: The 2.4 kb (or −α 2.4 ) deletion in the α-globin gene cluster (NG_000006.1) is an α + -thalassemia (α + -thal) allele. The molecular basis of −α 2.4 is a deletion from 36860 to 39251 of the α-globin gene cluster. It was reported by three research groups in 2005, 2012 and 2014, respectively. In routine thalassemia screening studies by this research group, we found an individual with the −α 2.4 /αα genotype and an Hb H (β4) disease patient whose genotype was – – SEA /−α 2.4 . Samples from the parents of the carrier of the −α 2.4 /αα genotype were collected to perform pedigree analysis, and the proband's mother's genotype was diagnosed to be – – SEA /−α 2.4 . The research revealed that the −α 2.4 allele exists in the population of southern Guangxi, People's Republic of China.